FEMA GRAS assessment of natural flavor complexes: Eucalyptus oil and other cyclic ether-containing flavoring ingredients. (September 2021) - Eisenbrand, Gerhard; Cohen, Samuel M.; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Davidsen, Jeanne M.; Harman, Christie L.; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) initiated a program for the re-evaluation of the safety of over 250 natural flavor complexes (NFCs) used as flavor ingredients. This publication, the sixth in the series, will summarize the re-evaluation of eight NFCs whose constituent profiles are characterized by significant amounts of eucalyptol and/or other cyclic ethers. This re-evaluation was based on a procedure first published in 2005 and subsequently updated in 2018 that evaluates the safety of naturally occurring mixtures for their intended use as flavoring ingredients. The procedure relies on a complete chemical characterization of the NFC intended for commerce and the organization of its chemical constituents into well-defined congeneric groups. The safety of the NFC is evaluated using the well-established and conservative threshold of toxicological concern (TTC) concept in addition to data on absorption, metabolism and toxicology of the constituents of the congeneric groups and the NFC under evaluation. Eight NFCs derived from the Eucalyptus, Melaleuca, Origanum, Laurus, Rosmarinus and Salvia genera were affirmed as generally recognized as safe (GRAS) under their conditions of intended use as flavor ingredients based on an evaluation of each NFC and the constituents and congeneric groups therein. Highlights: Safety evaluation of natural flavoring complexes containing eucalyptol. Evaluation used procedure developed by the FEMA Expert Panel for natural flavors. FEMA GRAS status determined/affirmed for 8 natural flavor complexes.